(untitled) (Perner’s Contacts, 2012)
In the beginning of article are briefly summarized methods for evaluation of vibrations on the human body often presented in fragmented form in standards, sanitary regulations and supplementary decrees and in various specialized publications dealing with vibration isolation and acoustics. Attention is paid to the recommended methodology for measuring vibration and subsequent processing of the measured data using frequency analysis. Acceleration RMS spectra of actively controlled driver’s seat are shown. Is carried out analysis of the results of driving tests conducted on test tracks at TATRA Kopřivnice.